Penerapan Metode RCM (Reliability Centered Maintenance) Pada Sistem Bahan Bakar (Fuel Oil System) Kapal TB.BLORO 10 - Mukhsin Al Amin; Nurvita Arumsari; Endah Wismawati; Icuk Kurniawan (Proceedings Conference on Marine Engineering and its Application, 2023)
- Main Engine is one of the important compartments on the ship which is located in theengine room. Has a function as a propulsion driver and as the main propulsion engine of theship. With such an important position, scheduling maintenance on the Main Engine is veryimportant to do. Because if the main engine is not running, then there will be no operation ofthe propulsion system on the ship and it will definitely be very detrimental to the ship owner.This final project attempts to answer these demands by creating a maintenance schedule for themain engine fuel system. In addition, the total operating costs which consist of running,maintenance and downtime costs will also be taken into consideration in determining themaintenance time. In this research, scheduling of main engine maintenance is carried out usingreliability centered maintenance which is used to select, develop, and create alternativemaintenance strategies based on operational, economic and safety criteria. Based on the failureanalysis using Failure Mode Effect Analysis, several component failures were identified, suchas the fuel injection pump (worn drive shaft, worn governor plunger, fuel gear pump lackinglubrication), injector nozzle (damaged nozzle tip, burrel plunger seal, M/E performance wasnot optimal ), gate valve (nut valve difficult to operate, disk valve has a leak, gasket on valve),fuel oil transfer pump (bearing wear, pump impeller corrosion, shaft corrosion), swing checkvalve (crusted disk valve, valve gasket), fuel filter (dirty fuel filter), quick closing valve (crusteddisk valve, gasket valve).